2017
DOI: 10.1371/journal.pone.0179160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of previous and current vaccination against influenza A(H1N1)pdm09, A(H3N2), and B during the post-pandemic period 2010-2016 in Spain

Abstract: BackgroundRecent studies suggest that the protective effect of the current influenza vaccine could be influenced by vaccination in previous seasons. We estimated the combined effect of the previous and current influenza vaccines from the 2010–2011 season to the 2015–2016 season in Spain.MethodsWe performed a test-negative case-control study in patients ≥9 years old. We estimated the influenza vaccine effectiveness (IVE) against influenza A(H1N1)pdm09, A(H3N2), and B virus.ResultsWe included 1206 influenza A(H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…This agrees with overall patterns of influenza circulation reported by the World Health Organization and others [13–17]. The predominance of influenza A(H1N1)pdm09 in Saint Petersburg (Russia), Moscow (Russia), Czech Republic, Turkey, France, Valencia (Spain), Mexico and Curitiba (Brazil), and B/Victoria-lineage in Beijing (China), agree with data reported for these countries [18–24]. Regional activity for A(H3N2) was reported in India, coinciding with our data obtained in the country’s Jammu and Kashmir state [24].…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with overall patterns of influenza circulation reported by the World Health Organization and others [13–17]. The predominance of influenza A(H1N1)pdm09 in Saint Petersburg (Russia), Moscow (Russia), Czech Republic, Turkey, France, Valencia (Spain), Mexico and Curitiba (Brazil), and B/Victoria-lineage in Beijing (China), agree with data reported for these countries [18–24]. Regional activity for A(H3N2) was reported in India, coinciding with our data obtained in the country’s Jammu and Kashmir state [24].…”
Section: Discussionsupporting
confidence: 91%
“…During these 2 seasons, the main circulating viruses matched the vaccine strains in Spain and other countries in Europe, 24,25 which contrasted with the low effectiveness of vaccination that was observed against nonsevere influenza; 26 however, this was consistent with the greater effectiveness that we found against severe influenza.…”
Section: Discussionsupporting
confidence: 71%
“…No significant differences between intraseasonal IVE estimates were observed over the three seasons analyzed. Prior studies (5,(25)(26)(27) found evidence for the waning of vaccine protection during a single season with increasing time since vaccination. However, waning of protection is not consistently observed in all seasons or populations.…”
Section: Discussionmentioning
confidence: 99%